2011
DOI: 10.1007/s12029-011-9325-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Escalated Imatinib Doses Compared with Sunitinib or Best Supportive Care, for the Treatment of People with Unresectable/Metastatic Gastrointestinal Stromal Tumours Whose Disease has Progressed on the Standard Imatinib Dose

Abstract: IntroductionWe conducted a systematic review of evidence on the effectiveness of imatinib at escalated doses of 600 mg/day or 800 mg/day for treatment of adults with unresectable or metastatic gastrointestinal stromal tumours (GIST), following progression on imatinib at the 400 mg/day dose, compared with sunitinib and/or ‘best supportive care’.MethodsElectronic searches were undertaken to identify relevant randomised controlled trials (RCTs), non-randomised studies, and case series reporting outcome data on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…A systematic review of randomized and nonrandomized studies to evaluate the efficacy of imatinib after dose escalation (600 mg/day or 800 mg/day) concluded that 1 in 3 patients had either a partial response or stable disease after the escalation of imatinib dose, and that 58.7% of these patients remained progression-free at 2 years' follow-up. 67 Another option for patients who are intolerant or resistant to imatinib is the multitargeted TKI sunitinib. Sunitinib inhibits c-KIT and PDGFR and other kinases, including the vascular endothelial growth factor receptors.…”
Section: Article In Pressmentioning
confidence: 99%
“…A systematic review of randomized and nonrandomized studies to evaluate the efficacy of imatinib after dose escalation (600 mg/day or 800 mg/day) concluded that 1 in 3 patients had either a partial response or stable disease after the escalation of imatinib dose, and that 58.7% of these patients remained progression-free at 2 years' follow-up. 67 Another option for patients who are intolerant or resistant to imatinib is the multitargeted TKI sunitinib. Sunitinib inhibits c-KIT and PDGFR and other kinases, including the vascular endothelial growth factor receptors.…”
Section: Article In Pressmentioning
confidence: 99%
“…Escalating the imatinib dose to 800 mg per day in this progressing population was demonstrated to achieve response or disease stabilization in one third of patients in a recent systematic review of published data [79], and this approach is considered as the treatment standard by many oncologists, although all of the available evidence is based on retrospective, observational studies. Sunitinib, a multi-TKI active against KIT, platelet-derived growth factor receptors and vascular endothelial growth factor receptors, is the standard treatment for patients progressing on or intolerant to imatinib.…”
Section: Management Of Advanced/metastatic Gistsmentioning
confidence: 99%
“…Median OS for imatinib (800 mg/day) and sunitinib both were less than 2 years. However, there were few data in this systematic review and those that were available were potentially biased, due to their nonrandomized nature [42].…”
Section: Discussionmentioning
confidence: 99%